Understanding Sace-Time The Philosophical Development of Physics from Newton to Einstein - Disalle, Robert (Press, 2013)
This book concerns the philosophy of space and time, and its connection with the evolution of modern physics. As these are already the subjects of many excellent books and papers – the literature of the “absolute versus relational” debate – the production of yet another book may seem to require some excuse. I don’t claim to defend a novel position in that controversy, or to defend one of the standard positions in a novel way. Still less do I pretend to offer a comprehensive survey of such positions and how they stand up in light of the latest developments in physics